Strengthening The Presidential System by Simplifying Parliamentary Political Parties By Maximized Parliamentary Threshold Figures - Rona Asfuzi Rambe; Benito; Andryan; Dedi Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The parliamentary threshold is the minimum vote requirement for political parties in the general election to be included in determining the seats of the DPR-RI in Senayan. Problems arise when the parliamentary threshold is unable to simplify political parties so that it affects the stability of the presidential government. This study aims to determine how the design of the simplification of the parliamentary threshold is in strengthening the presidential system and to determine the relationship between the simplification of political parties and the presidential system. This type of research is normative research that uses secondary data sources. Based on the results of the study, it is known that the parliamentary threshold always changes in every election, starting from the first election to the 2024 election. The design to achieve the goal of simplifying parliamentary political parties to strengthen the presidential system is to increase the parliamentary threshold. Furthermore, there is a relationship between the simplification of political parties and the presidential system. If the number of political parties that win seats in parliament is small, then the presidential system becomes effective and government stability is maintained. However, if the number of parties that exceed the threshold is large, policy making will affect government stability, so that there will be many conflicts of interest, and government stability becomes unstable.